Validity and effects of placement of velocity-based training devices - Fritschi, R.; Seiler, J.; Gross, M. (Sports, 2021)
Velocity-based training (VBT) is a resistance training method by which training variables are manipulated based on kinematic outcomes, e.g., barbell velocity. The better precision for monitoring and manipulating training variables ascribed to VBT assumes that velocity is measured and communicated correctly. This study assessed the validity of several mobile and one stationary VBT device for measuring mean and peak concentric barbell velocity over a range of velocities and exercises, including low- and high-velocity, ballistic and non-ballistic, and plyometric and non-plyometric movements, and to quantify the isolated effect of device attachment point on measurement validity. GymAware (r = 0.90-1, standard error of the estimate, SEE = 0.01-0.08 m/s) and Quantum (r = 0.88-1, SEE = 0.01-0.18 m/s) were most valid for mean and peak velocity, with Vmaxpro (r = 0.92-0.99, SEE = 0.02-0.13 m/s) close behind. Push (r = 0.69-0.96, SEE = 0.03-0.17 m/s) and Flex (r = 0.60-0.94, SEE = 0.02-0.19 m/s) showed poorer validity (especially for higher-velocity exercises), although typical errors for mean velocity in exercises other than hang power snatch were acceptable. Effects of device placement were detectable, yet likely small enough (SEE < 0.1 m/s) to be negligible in training settings.